1979
DOI: 10.1177/002203457905800223011
|View full text |Cite
|
Sign up to set email alerts
|

Disturbances and Defects in Enamel Development

Abstract: Ameloblastic disturbances are correlated with defects in enamel. Experimental disturbances created by tetracyclines, fluorides, and antimitotic drugs are emphasized. Cellular alterations are shown to interfere with both matrix production and secretion. Defects in enamel formation are characterized by abnormal crystal size and distribution. Further research in normal and particularly abnormal enamel development is needed to establish: 1. exact mode of matrix secretion and its relation to crystal nucleation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1980
1980
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…The presence of light pigmentations on occlusal grooves in one of the molars from the group exposed to tetracycline (130 mg/kg), coincides with reports of several authors (15,16), who refer that dental alterations caused by these drugs are optically visible. Likewise, all molars exposed to tetracycline showed hypomineralized enamel, relating to several published studies (15,17), where it has been widely made known that tetracycline cause structural and functional changes in ameloblasts and in immature enamel; therefore, its use as positive control is valid to assess alterations in dental enamel caused by medications and other toxic substances in lab animals (15,17).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The presence of light pigmentations on occlusal grooves in one of the molars from the group exposed to tetracycline (130 mg/kg), coincides with reports of several authors (15,16), who refer that dental alterations caused by these drugs are optically visible. Likewise, all molars exposed to tetracycline showed hypomineralized enamel, relating to several published studies (15,17), where it has been widely made known that tetracycline cause structural and functional changes in ameloblasts and in immature enamel; therefore, its use as positive control is valid to assess alterations in dental enamel caused by medications and other toxic substances in lab animals (15,17).…”
Section: Discussionsupporting
confidence: 90%
“…Likewise, all molars exposed to tetracycline showed hypomineralized enamel, relating to several published studies (15,17), where it has been widely made known that tetracycline cause structural and functional changes in ameloblasts and in immature enamel; therefore, its use as positive control is valid to assess alterations in dental enamel caused by medications and other toxic substances in lab animals (15,17). …”
Section: Discussionmentioning
confidence: 81%
“…tetracyclines primarily affect amelogenesis at the TetracycHoes are rapidly incorporated into time of formation of the enamel tnatrix (16,26). many cells both in vivo and in vitro, antJ Observations at the ultrastructural level have ultrastructoral changes of secretory--ameloblasts indicated that interference with matrix form-in rats induced by these drugs have been atioti and initial mineralization might be a described (7,18,19). These obser\'ations were sequela to injur)' of secretor)' ameloblasts (14).…”
Section: High Doses Of Various Tetracyclines Inducementioning
confidence: 99%
“…In laboratory animals, TC at dosage levels higher than 130 mg/kg is known to create disturbanees in enatnel and dentine formation when administered during odontogenesis. Thus, in rat enamel, TC has been shown to induce eellular alterations, to interfere with protein synthesis and with the delivery system of the secretory proteins (15). The action of TC upon the organic component of the mineralization process has been studied in vitro and it has been shown that TC uptake inhibits amorphous crystalline transformation (16).…”
Section: Discussionmentioning
confidence: 99%